Political theory and the European constitution - Dobson, Lynn; Føllesdal, Andreas (Routledge, 2004)
This timely volume provides one of the first critical assessments of the draft Constitution (released by the Convention on the future of Europe) from the vantage point of political theory.
Keywords: Constitutional law -- European Union countries.; Droit constitutionnel -- Pays de l'Union européenne.; LAW -- Constitutional.; LAW -- Public.; Constitutional law; European Union countries